Telaah terhadap Konsep Pendidikan Karakter Kementerian Pendidikan dan Kebudayaan - Permata, Firdaus; Thoyyar, Husni (Tsamratul Fikri | Jurnal Studi Islam, 2016)
National character education in the perspective of Islamic education is only a small part of the character. Character education or moral education is only like a salt in the oceans. The concept of morality in Islam has a very close relationship with faith and sharia, even is the unity that cannot be separated. Therefore, to realize the noble character in themselves a Muslim, the first thing to do is to build a strong faith, and implement all the provisions of the existing Islamic in the Quran and Hadith, which carry out or perform righteous deeds. With the two in this way, noble character will be formed and sturdiness. The concept of character education in Indonesia is already there, but not yet perfect in the perspective of Islamic education. This is because the reference value and the source of which can still be interpreted any, and also the concept of character education from the Ministry of Education and Culture has not shown a model of the ideal human character, because they do not have a clear model and empirical. While the Prophet Muhammad has been proven to make an ignorant society turn into people who are qualified. on according to the Quran includes education to form four following manners: a) honest; b) discipline; c) responsibility; and d) hard work, which are based on the faith education. tors , contents, methods, teaching media, space and time, and showed a close relevance to the development of education today, education in general and education in particular with the Islamic style.